The inhibitory effect of liposome‐encapsulated indomethacin on inflammation and platelet aggregation - (:unkn) unknown (My University, 1988)
Abstract— A comparison has been made between liposome‐encapsulated and free indomethacin for their anti‐inflammatory activities in the carrageenan paw oedema test in rats, and their inhibitory effect on platelet aggregation induced by adenosine 5‐diphosphate (ADP) in‐vitro. Free indomethacin, 3 mg kg−1, strongly inhibited carrageenan‐induced oedema and a similar inhibitory activity was shown by 0.3 mg kg−1 of encapsulated drug. For the inhibition of platelet aggregation, the threshold concentration of free drug was 0.559 mM. At this concentration, at least 5 min incubation was needed to achieve 12.5% and 45 min for 50% inhibition. The inhibition was much stronger with encapsulated drug, and pre‐incubation of 28 μM encapsulated drug for 10 min with platelet‐rich plasma before addition of ADP completely inhibited platelet aggregation. 1988 Royal Pharmaceutical Society of Great Britain